Reversible Posterior Leukoencephalopathy Syndrome Induced by Pazopanib - Chelis, Leonidas (BioMed Central, 2012)
BACKGROUND: The reversible posterior leukoencephalopathy syndrome is a clinical/radiological syndrome characterized by headache, seizures, impaired vision, acute hypertension, and typical magnetic resonance imaging findings. There are several reports in the literature that depict its occurrence in cancer patients. The list of common anticancer and supportive care drugs that predispose to reversible posterior leukoencephalopathy syndrome is expanding and includes not only a large number of chemotherapeutic agents but also an increased number of new targeted drugs, particularly angiogenesis inhibitors such as bevacizumab,sorefenib and sunitinib. Pazopanib is an oral tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and c-Kit which after a positive phase III randomized clinical trial in patients with advanced renal cell cancer received FDA approval for the treatment of advanced renal cell carcinoma. Until now no cases of reversible posterior leukoencephalopathy syndrome induced by pazopanib have been reported. CASE REPORT: We present the case of a 40 years old female patient with heavily pre-treated metastatic renal cell carcinoma who received pazopanib as salvage treatment. After 21 days of pazopanib therapy the patient referred to the emergency department with epileptic seizure, impaired vision at both eyes and headache. MRI of the brain revealed subcortical oedema at the occipital and parietal lobes bilaterally. She was treated with anticonvulsants, i.v. administration of mannitol and antihypertensives and she recovered completely from her symptoms and was discharged on the tenth hospital day. A brain MRI performed 3 weeks after showed that the subcortical oedema had been subsided. CONCLUSION: In conclusion this is the first case of pazopanib induced reversible posterior leukoencephalopathy syndrome. Although usually reversible, this syndrome is a serious and potentially life threatening adverse effect, if untreated, that should be considered by physicians treating metastatic renal cell carcinoma patients with pazopanib.